Towards the translation of multilingual Bible study guides for the Seventh-Day Adventist Church in Southern Africa - J. A. Naudé; G. Gelderbloem (Acta Theologica)
Southern Publishing Association, the publishing house of the SA Seventh-day Adventist Churches, provides Bible Study Guides for its church members. In South Africa, the English source text is translated into five languages, namely Sesotho, isiXhosa, TshiVenda, isiZulu and Afrikaans. The study guides are used for home study and in Sabbath School classes. The specific aims of the article include: to discover, by means of an empirical study, whether the translations are meeting the cultural and linguistic needs of the target audience and to determine their views on the current Bible Study Guides; to explore the future of translation in a multilingual, democratic South Africa; to ascertain by means of a survey the difficulties the translators face and to suggest improvements; to establish, by analysis, how the text can be translated functionally; and to establish the effect of globalisation and whether it would be possible to localise the source texts.